Beyond transvaginal retrieval: laparoscopic oocyte aspiration in three challenging cases - Nair, Sreelakshmy R.; Subramanian, Subhadra; Pappachan, Cyriac; Pappachan, Skariah (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Laparoscopic oocyte retrieval is a surgical method for retrieving oocytes, primarily used when standard transvaginal approaches are not feasible due to anatomical or pathological barriers. This technique is especially relevant for fertility preservation in patients with pelvic tumors, inaccessible ovaries, or when concurrent pelvic surgery is indicated. We report 3 cases in which transvaginal approach was difficult and hence laparoscopy was used.